Growth Response of Oil Palm Seedlings (Elaeis guineensis Jacq.) to A Mixture of Oil Palm Waste Compost and Voc Vermin Fertilizer in the Main Nursery - Situmeang, Greselia Pionita; Maryani, Anis Tatik; Salim, Helmi (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: This research aims to examine the planning and implementation process of educational institutions at SDUT Masyitoh Muslimat NU Bandungrejo. This research focuses on understanding the strategic steps taken by school administration in achieving educational goals, the role of stakeholders, and the challenges faced during the planning and implementation stages. Research Methods: Using a qualitative descriptive approach, data was collected through interviews and observations involving school administrators, teachers and related community members. Finding/Results: The research results show that the planning process at SDUT Masyitoh Muslimat NU is based on the school's vision and mission, focusing on holistic student development, integrating religious values, and academic excellence. Implementation strategies include curriculum design, extracurricular activities, and community involvement that are aligned with the goals of educational institutions. However, this research also identified certain obstacles, such as limited resources and administrative challenges, that affected the smooth implementation of the planned program. Conclusion: This research concludes by offering suggestions to improve the effectiveness of educational planning and implementation at SDUT Masyitoh Muslimat NU Bandungrejo, thereby contributing to improved outcomes for students and the institution as a whole.